2010
DOI: 10.1182/blood-2009-10-248518
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab plus Peg-interferon-α/ribavirin compared with Peg-interferon-α/ribavirin in hepatitis C–related mixed cryoglobulinemia

Abstract: Treatment of hepatitis C (HCV)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
148
1
10

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 245 publications
(166 citation statements)
references
References 36 publications
7
148
1
10
Order By: Relevance
“…This multicenter, retrospective study including a large patients' series further supports and expands the results of previous reports showing the usefulness of rituximab in active MCs [9][10][11][12][24][25][26][27][28][29][30][31]. The positive effects of this treatment were particularly evident for the most frequent disease manifestations such cutaneous vasculitic lesions, i.e.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This multicenter, retrospective study including a large patients' series further supports and expands the results of previous reports showing the usefulness of rituximab in active MCs [9][10][11][12][24][25][26][27][28][29][30][31]. The positive effects of this treatment were particularly evident for the most frequent disease manifestations such cutaneous vasculitic lesions, i.e.…”
Section: Discussionsupporting
confidence: 86%
“…In this respect, previous studies clearly demonstrated that, when present, the increase of HCV viral load did not affect the liver texts as well as other clinico-serological parameters [11,12]. The lack of hepatic toxicity has been further evidenced by a recent clinical observation in patients with HCVrelated MCs and advanced cirrhosis treated by rituximab [29,49]; besides its efficacy on cryoglobulinemic vasculitis the treatment was followed by an improvement of liver function. It is possible to ascribe this unexpected hepatic amelioration to the depletion of CD20+ B-cells induced by rituximab through two different mechanisms; firstly, the drug may reduce also the hepatic B-cell infiltrates conditioning liver damage and, indirectly, it may improve the Kupffer cell function as consequence of serum cryoglo-bulin level reduction [28].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations